2013
DOI: 10.1038/hr.2013.131
|View full text |Cite
|
Sign up to set email alerts
|

Differences in vascular reactivity between pregnant women with chronic hypertension and preeclampsia

Abstract: The purpose of this study was to evaluate the distinct pathogenic mechanisms underlying chronic hypertension in pregnancy and preeclampsia in terms of oxidative stress and vascular reactivity. A total of 17 women with uncomplicated pregnancies, 30 women with preeclampsia and 17 women with chronic hypertension were evaluated. We measured serum derivatives of reactive oxygen metabolites (d-ROMs; marker of oxygen free radicals), flow-mediated vasodilation (FMD; marker of endothelial function) and intima-media thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
39
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 31 publications
1
39
0
1
Order By: Relevance
“…Our results were consistent with previous studies. Mori et al 27 reported that BP in women with preeclampsia significantly decreased a month after delivery, whereas BP remained higher than in normotensive mothers. Furthermore, nighttime systolic BP in the ambulatory setting was significantly (P = 0.030) elevated in Swedish women with preeclampsia compared with those without preeclampsia even 11 years after delivery, although this was not the case for the other BP data (P ⩾ 0.073).…”
Section: Discussionmentioning
confidence: 97%
“…Our results were consistent with previous studies. Mori et al 27 reported that BP in women with preeclampsia significantly decreased a month after delivery, whereas BP remained higher than in normotensive mothers. Furthermore, nighttime systolic BP in the ambulatory setting was significantly (P = 0.030) elevated in Swedish women with preeclampsia compared with those without preeclampsia even 11 years after delivery, although this was not the case for the other BP data (P ⩾ 0.073).…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, when Mori et al [93 ]measured FMD in women who had had PE and those with a normal pregnancy, they found that the vasodilator response (significantly reduced in the preeclamptic group during pregnancy) normalized 1 month after delivery. …”
Section: Evaluation Of Endothelial Dysfunction By Fmdmentioning
confidence: 99%
“…8<11 We have also previously reported that plasma triglycerides (TG) and lowdensity lipoprotein cholesterol (LDL-C) levels were higher, and insulin resistance was greater, in women with preeclampsia. 3,5 Thus, women with preeclampsia may be at increased risk for CVD.…”
mentioning
confidence: 99%